Echocardiographic and Electrocardiographic Abnormalities Among Elderly Adults With Cardiovascular Disease in Rural South Africa. Issue 11 (November 2021) - Ferro, Enrico G.; Abrahams-Gessel, Shafika; Jardim, Thiago Veiga; Wagner, Ryan; Gomez-Olive, F. Xavier; Wade, Alisha N.; Peters, Ferande; Tollman, Stephen; Gaziano, Thomas A.
Abstract : Background: Sub-Saharan Africa is undergoing an epidemiological transition fueled by the interaction between infectious and cardiovascular diseases. Our cross-sectional study aimed to characterize the spectrum of abnormalities suggesting end-organ damage on ECG and transthoracic echocardiograms (TTE) among older adults with cardiovascular diseases in rural South Africa. Methods: The prevalence of ECG and TTE abnormalities was estimated; χ 2 analyses and multivariable logistic regressions were performed to test their association with sex, hypertension, and other selected comorbidities. Results: Overall, 729 ECGs and 155 TTEs were completed, with 74 participants completing both. ECG evaluation showed high rates of left ventricular hypertrophy (LVH, 36.5%) and T wave abnormalities (13.6%). TTE evaluation showed high rates of concentric LVH (31.6%), with moderate-severe (56.8%) diastolic dysfunction. Participants with hypertension showed more cardiac remodeling on ECG by LVH (45.4% versus 22.1%, P <0.01), and TTE by concentric LVH (42.5% versus 8.2%, P <0.01) and increased left ventricular mass (58.5% versus 20.4%, P <0.0001). In multivariable logistic regression, systolic blood pressure remained significantly associated with LVH on ECG (adjusted odds ratio, 1.03 per mm Hg [95% CI, 1.03–1.04], P <0.0001) and increased left ventricular mass on TTE (adjusted odds ratio, 1.04 per mm Hg [95% CI, 1.01–1.06], P =0.001). Male participants (n=326, 40.2%) were more likely than females (n=484, 59.8%) to show ECG abnormalities like LVH (45% versus 30.8%, P <0.01), whereas females were more likely to show TTE abnormalities like concentric LVH (40.8% versus 13.5%, P <0.01) and increased left ventricular mass (58.4% versus 23.1%, P <0.0001). Similar results were confirmed in multivariable models. Conclusions: Our findings suggest that cardiovascular diseases are widespread in rural South Africa, with a larger burden of hypertensive heart disease than previously appreciated, and define the severity of end-organ damage that is already underway. Local health systems must adapt to face the growing burden of hypertension, as suboptimal rates of hypertension diagnosis and treatment may dramatically increase the heart failure burden. Abstract : Supplemental Digital Content is available in the text.